(untitled) - Wilson, Ken (Oxford, 2007)
Smart Choice is a complete four-skills course with a special focus on conversation. With its straightforward approach, the series requires minimal preparation, while allowing plenty of opportunity for supplementation. Each page of Smart Choice offers a self-contained lesson, focusing on a particular skill, and closes with a discussion activity.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Problems, exercises etc.,Study and teaching,Câu hỏi và bài tập,Học và dạy